Haplotypic structure of ABCB1/MDR1 gene modifies the risk of the acute allograft rejection in renal transplant recipients - Bandur, Stepan; Petrasek, Jan; Hribova, Petra; Novotna, Eva; Brabcova, Irena; Viklicky, Ondrej (Transplantation, 2008)
BACKGROUND: Bioavailability of tacrolimus (Tac) and cyclosporine is determined by cytochrome P450IIIA and by P-glycoprotein encoded by the CYP3A4/CYP3A5 and ABCB1 genes. Polymorphisms in these genes have been suggested to influence acute rejection and pharmacokinetics in renal transplantation. We aimed to validate these findings in a haplotype analysis. METHODS: A total of 832 renal transplant recipients were genotyped for the CYP3A4 -288A>G, CYP3A5 +6986G>A, ABCB1 +1236C>T, +2677G>T>A, and +3435C>T polymorphisms. Their association with acute rejection and with pharmacokinetic parameters was analyzed in haplotype models. RESULTS: Apart from human leukocyte antigen-DR mismatches, delayed graft function and age at renal transplantation, acute rejection was also predicted by the [ABCB1 +1236C; +2677G; +3435T] haplotype. Allograft survival was determined by donor age, age at renal transplantation, delayed graft function, cold ischemia, and history of more than two acute rejections. Homozygotes for the [CYP3A4 -288A; CYP3A5 +6986G] haplotype achieved earlier therapeutic concentrations of Tac and a higher concentration to dose ratio at week 1. ABCB1 haplotypes did not influence pharmacokinetic parameters. CONCLUSIONS: ABCB1 haplotypes modify the risk of acute rejection, suggesting that ABCB1 allelic arrangement is a stronger regulator of P-glycoprotein activity than single polymorphisms. The risk of acute rejection determined by ABCB1 is independent of pharmacokinetic parameters. CYP3A haplotypes control the bioavailability of Tac, but do not modify the risk of acute rejection.
Keywords: alely; Polymorphism, Single Nucleotide; haplotypy; Humans; Case-Control Studies; ATP Binding Cassette Transporter, Subfamily B, Member 1; lidé středního věku; dítě; studie případů a kontrol; kohortové studie; Child; Graft Rejection; jednonukleotidový polymorfismus; Female; rizikové faktory; mladý dospělý; dospělí; Aged; Haplotypes; přežívání štěpu; Alleles; senioři; lidé; Genotype; ATP Binding Cassette Transporter, Subfamily B; Transplantation, Homologous; Cohort Studies; předškolní dítě; Adult; transplantace ledvin; P-glykoprotein; ženské pohlaví; Male; Middle Aged; Retrospective Studies; P-glykoproteiny; Adolescent; Kidney Transplantation; Young Adult; genotyp; retrospektivní studie; mužské pohlaví; homologní transplantace; Child, Preschool; Graft Survival; rejekce štěpu; mladiství; Risk Factors